2023
DOI: 10.1002/epi4.12799
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy is an important feature of KBG syndrome associated with poorer developmental outcome

Nathan Buijsse,
Floor E. Jansen,
Charlotte W. Ockeloen
et al.

Abstract: ObjectiveThe aim of this study was to describe the epilepsy phenotype in a large international cohort of patients with KBG syndrome and to study a possible genotype–phenotype correlation.MethodsWe collected data on patients with ANKRD11 variants by contacting University Medical Centers in the Netherlands, an international network of collaborating clinicians, and study groups who previously published about KBG syndrome. All patients with a likely pathogenic or pathogenic ANKRD11 variant were included in our pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…We recommend further research to delve more into types of seizures experienced. Buijsse et al 7 discovered that those with simultaneous KBG and epilepsy diagnoses more often had moderate to severe intellectual disability compared to those without a history of epilepsy. Their finding is significant given that seizures occur in a large portion of the KBG syndrome population (up to 33%), with onset occurring during infancy through mid-teens and often recurring at or shortly after adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recommend further research to delve more into types of seizures experienced. Buijsse et al 7 discovered that those with simultaneous KBG and epilepsy diagnoses more often had moderate to severe intellectual disability compared to those without a history of epilepsy. Their finding is significant given that seizures occur in a large portion of the KBG syndrome population (up to 33%), with onset occurring during infancy through mid-teens and often recurring at or shortly after adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…These include a range of seizures such as focal and generalized seizures, tonic-clonic and absence seizures, myoclonic seizures, and unclassified sleep-related seizures. 7 Some individuals may exhibit electroencephalogram (EEG) abnormalities without clinically evident seizures. 8 Those with KBG syndrome are more susceptible to epilepsy, which occurs in a significant percentage of cases, 9 although epilepsy is not formally recognized as a defining characteristic of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…While epilepsy syndromes are uncommon in KBG syndrome, a recent multicentre study combining original and historical patients identified 12/63 (19%) epilepsy-affected KBG patients with an epilepsy syndrome (most were generalised epilepsy syndromes) and with associated developmental and/or epileptic encephalopathy (DEE) [10] . Here we describe a patient with LGS, a phenotype also described in three other patients with KBG syndrome [10] , [19] . KBG syndrome-affected patients with epilepsy have a significantly poorer neurodevelopmental outcome compared to those without epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures occur in KBG syndrome, mostly as part of a developmental encephalopathy [9] , [10] , [11] . Recently, Buijsse et al reported 26/75 patients with epilepsy (original and historical literature combined), most of whom were classified by International League Against Epilepsy (ILAE) criteria, as having generalized epilepsy (15/38 or 39 % patients), focal epilepsy 12/38 (31.6 %), or combined focal and generalized epilepsy (11/38 or 31.6 %) [10] . Distinctive epilepsy syndromes were identified in only few patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation